Iklan One Piece We Are One Episode 2 Dalam Kerangka Analisis Semiotik Roland Barthes - Iswahyu Pranawukir; Yazid Akromudin; Mayang Riyantie; Maria Jashinta Elisabet Hamboer; Alamsyah Alamsyah (Cakrawala - Jurnal Humaniora, 2023)
In this research, the writer chose the object of an advertisement for a phenomenal comic series, namely One Piece. The results of the study show that from the denotative side tells about the life of urban residents in the city center, from the connotative side it equality and from the mythical side it conveys the influence of the One Piece story on women's enthusiasm in realizing dreams. The results of the study also found 5 Roland Barthes narrative codes, including: hermeneutic code used in the dialogue about people who’ve never read One Piece mean they haven’t truly live. Proairetic code is used influence reading One Piece. Semantic code is in the description of the main character's work. Symbolic code can be seen in the antithesis of the main character's character, namely the nature of his partner. The cultural code is found in the depiction of the main character and his partner who live together even though they are not married.